Dinamika Urbanisasi dan Transformasi Lahan Terbangun di Provinsi Riau 2020-2030 (Model Spasial dengan Pendekatan Zonasi ClockBoard) - Widya Putra, Dimas; Setiawan, Alifianto; fadlly, fariha (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2025)
The increasing urbanization and expansion of built-up areas in Riau Province have led to significant changes in land use patterns and population distribution. This study analyzes urbanization patterns and built-up land distribution in 12 districts/cities for the years 2020 and projected 2030, utilizing GHSL-SMOD data and the ClockBoard zoning system. GHSL is used to identify urban centers, population density, and built-up area characteristics, while ClockBoard provides a uniform geometric zoning framework to facilitate spatial analysis.The results reveal varied urban growth patterns across regions. Pekanbaru and Dumai show high density and significant expansion, while Bengkalis, Rokan Hulu, and Indragiri Hilir demonstrate clustered and linear growth patterns. Some districts, such as Siak and Kepulauan Meranti, exhibit urban sprawl. The development of urban centers does not always correspond to administrative size but is influenced by zoning structure and land-use density. The integration of GHSL-SMOD with ClockBoard proves effective in mapping urbanization variations and provides a solid foundation for more accurate, structured, and sustainable regional development planning.